Flexible customization of the self‐assembling abilities of short elastin‐like peptide Fn analogs by substituting N‐terminal amino acids. Issue 10 (13th July 2022) - Suyama, Keitaro; Shimizu, Marin; Maeda, Iori; Nose, Takeru
Abstract: Elastin‐like peptides (ELPs) are thermoresponsive biopolymers inspired by the characteristic repetitive sequences of natural elastin. As ELPs exhibit temperature‐dependent reversible self‐assembly, they are expected to be biocompatible thermoresponsive materials for drug delivery carriers. One of the most widely studied ELPs in this field is the repetitive pentapeptide, (VPGXG)n . We previously reported that phenylalanine‐containing ELP (Fn) analogs, in which the former Val residue of the repetitive sequence (VPGVG)n is replaced by Phe, show coacervation with a short chain length (n = 5). Owing to their short sequences, Fn analogs are easily modified in amino acid sequences via simple chemical synthesis, and are useful for investigating the relationship between peptide sequences and temperature responsiveness. In this study, we developed Fn analogs by replacing Phe residue(s) with other amino acids or introducing another amino acid at the N ‐terminus. The temperature responsiveness of the Fn analogs changed drastically with the substitution of a single Phe residue, suggesting that aromatic amino acids play an important role in their self‐assembly. In addition, the self‐assembling ability of Fn was enhanced by increasing the bulkiness of the N ‐terminal amino acids. Therefore, the N ‐terminal residue was considered to be important for hydrophobicity‐induced intermolecular interactions between the peptides during coacervation. Abstract :